Equate the last 2 parts of the statement by the 1st statement to make 2 equations
a/(b + c) = b/(c + a)
a/(b + c) = c/(a + b)
Multiply each by their LCD
a² + ac = b² + bc
a² + ab = c² + bc
Subtract the 1st equation from the 2nd equation
c² - b² = ab - ac
Transpose to the left
c² - b² + ac - ab = 0
Factor monomially and by special factoring
(c + b)(c - b) + a(c - b) = 0
Factor the groups
(c - b)(c + b + a) = 0
There are 2 cases
c - b = 0 or c + b + a = 0
Thus,
b = c (Let it be case A) or a + b + c = 0 (Let it be case B)
---case A---
Since b = c and
a² + ac = b² + bc,
Substitute b for all c
a² + ab = b² + b²
Add and transpose to the left
a² + ab - 2b² = 0
factor
(a - b)(a + 2b) = 0
There are 2 cases for case A
a = b or a = -2b
For a = b = c, The value for r is r = a/(b + c) = a/(a + a) = a/2a = 1/2
For b = c,a = -2b, The value for r is r = a/(b + c) = (-2b)/(b + b) = -2b/2b = -1
---case B---
a + b + c = 0
Thus,
b + c = -a
The value for r is r = a/(b + c) = a/(-a) = -1
Thus, the only values for r that we got is 1/2 (from case A) and -1 (from both cases). Therefore, the answer is (c) 1/2 or -1.
(Note that there are some undefined values for r, specifically when b + c = 0, a + c = 0, and/or a + b = 0, but this does not affect our answer.)
^_^
^_^